Fabrication and characterisation of chemical vapour deposition grown branched carbon nanotube arrays - Leahy, Rory (Trinity College (Dublin, Ireland). School of Physics, 2007)
The fabrication, optimisation and characterisation of arrays of straight and junction multiwall carbon nanotubes (MWNTs) is presented in this thesis. A detailed description of the design and fabrication of the chemical vapour deposition (CVD) system used for their production is presented. Various carbon nanotube (CNT) geometries produced during the optimisation of the CVD parameters, such as mats, vertically aligned forests and long CNTs are presented and discussed.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin